PENGARUH PEMANFAATAN PERPUSTAKAAN SEKOLAH TERHADAP HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 21 PEKANBARU - Dasman Sangkelana Putra; Hendri Marhadi; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was motivated by the importance of the role of the school library as a source of learning in school. As a source of learning, the school library must be used by the students for all subjects in school, one social studies. This study aims to determine the effect of the use of the school library to the learning outcomes social studies fifth grade students of SDN 21 Pekanbaru. By doing the research is expected to provide benefits to improve the utilization of the school library as a learning resource. This research is a quantitative research with survey method. The study was conducted in SDN 21 Pekanbaru sample fifth grade students who are 54 students. Researcher using questionnaire instrument to obtain data on the use of libraries in SDN 21 Pekanbaru, and the results of social studies students of fifth grade was obtained from the value of daily tests social studies students. Based on analysis of data obtained in this study can be concluded that there is no significant relationship between the use of the school library to the learning outcomes social studies fifth grade students of SDN 21 Pekanbaru. The results of the questionnaire answers given to the students indicate that the use of the library is not maximized, because not all students who use the school library with a good learning social studies. The results of the data analysis scores thitung -0.499 and ttable 2.007. Because thitung smaller than ttable, it can be concluded that there is no significant effect between the use of the school library to the learning outcomes social studies fifth grade students of SDN 21 Pekanbaru. That is, use of the library provides very little effect or no significant effect on the results of social studies fifth grade students of SDN 21 Pekanbaru, at only 0.5%. Therefore, researchers gave suggestions to further improve the utilization of SDN 21 Pekanbaru library in order to improve student learning outcomes. The entire school community should contribute to maintain and utilize the library in order to obtain the maximum results from the use of the library. Keywords: Use of Library, Learning Outcome